Constructing the Active Sites of an Artificial Hydrolase Using Mercaptoethanol as a Destructive Agent - Dar-Fu Tai; Sue-Chen Wang; Lisa Chen; Venkatachalam Angamuthu; Chung-Yin Lin (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
In the present study, (N-acryloyl-L-cysteine-benzyl amide)2 (Acryl-L-Cys-NHBn)2, N-acryloyl-L-histidine-benzyl amide (Acryl-L-His-NHBn), and N-acryloyl-aspartic acid-benzyl amide (Acryl-L-Asp-NHBn) were chemo-enzymatically synthesized from Boc-L-amino acids. Then, a mixture of these acryl amino acid monomers was copolymerized to form polymers. The resulting random polymers were then activated after a mercaptoethanol-triggered reduction of disulfide linkages to thiol. The activated polymer demonstrated substrate selectivity, turnover, and rate enhancement in catalyzing the hydrolysis of the esters of Cbz-glycine. The results demonstrated that radical polymerization can facilitate the task of preparing synthetic macromolecules capable of enzyme-like catalytic turnover, substrate selectivity, and rate enhancement. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).